2006
DOI: 10.1007/s00455-006-9024-9
|View full text |Cite
|
Sign up to set email alerts
|

Is the Anatomical Protrusion on the Posterior Hypopharyngeal Wall Associated with Cadavers of Only the Elderly?

Abstract: Cricopharyngeal bars are commonly seen on a barium swallow radiologic examination and represent the failure of the cricopharyngeus to relax. Traditionally, the bars have been considered as functional or physiologic protrusions. Recently, anatomical cricopharyngeal protrusion has been found in about 30% of cadavers of the elderly, suggesting that such a structural change may become a physical barrier that affects the normal deglutition in a living person. This suggests that such a radiographic finding should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In this study we investigated the variability in the macroscopic morphology of this muscle, and found that in about one third of the examined cases the muscle showed a deformation that was causing a constriction or recess on the pharyngoesophageal transition. These findings seem to agree with those of other studies about the structural changes of the CPM in the elderly cadaver,15, 16 and suggest that the consequent protrusion in the pharyngeal lumen in the living person may become a physical barrier affecting normal swallowing and causing increased intrabolus pressures. The cricopharyngeal protrusion can appear as a cricopharyngeal bar on the lateral radiographs of barium swallows.…”
Section: Discussionsupporting
confidence: 92%
“…In this study we investigated the variability in the macroscopic morphology of this muscle, and found that in about one third of the examined cases the muscle showed a deformation that was causing a constriction or recess on the pharyngoesophageal transition. These findings seem to agree with those of other studies about the structural changes of the CPM in the elderly cadaver,15, 16 and suggest that the consequent protrusion in the pharyngeal lumen in the living person may become a physical barrier affecting normal swallowing and causing increased intrabolus pressures. The cricopharyngeal protrusion can appear as a cricopharyngeal bar on the lateral radiographs of barium swallows.…”
Section: Discussionsupporting
confidence: 92%
“…These findings need to be considered in light of previous findings of nonobstructive and obstructive bars seen in asymptomatic elderly individuals 3, 19–21. Leonard et al reported asymptomatic CPBs of all sizes in more than 30% of 88 elderly subjects without dysphagia 19.…”
Section: Discussionmentioning
confidence: 79%